An Examination of Human Resource Management Practices’ Influence on Organizational Commitment and Entrenchment - Alba Couto Falcão Scheible; Antonio Virgílio Bittencourt Bastos (BAR: Brazilian Administration Review, 2013)
This study sought to understand how the employee perceptions of human resource management practices influence both organizational affective commitment and entrenchment. It represents advancement towardsdiscriminant validity of such linkages that develop between individuals and the organizations they work for. A survey of 307 participants was conducted in an Information Technology company in Brazil. It was found that affective commitment has a strong and positive relationship with perceptions of HRM practices, while entrenchment is also related, but in a very weak fashion. Training and development practices showed better fit with the expected results of such practices in the organization studied, strongly affecting commitment, but not enhancing entrenchment. Even if not generalizable, these results strengthen the research stream that defends that commitment and entrenchment are separate constructs.